Study protocol of the CAREST-trial: a randomised controlled trial on the (cost-) effectiveness of a CBT-based online self-help training for fear of cancer recurrence in women with curatively treated breast cancer. Issue 1 (December 2016) - van Helmondt, Sanne; van der Lee, Marije; de Vries, Jolanda
Abstract Background One of the most prevalent long-term consequences of surviving breast cancer is fear of cancer recurrence (FCR), which is associated with higher (mental) healthcare costs and lower surveillance rates. The majority of breast cancer survivors report a need for professional help in dealing with FCR. An easy-accessible and cost-effective evidence‐based psychological intervention for reducing FCR is lacking. In the current study an online self-help training to reduce FCR will be evaluated. In addition, the secondary aim of this study is to identify factors that predict whether women can benefit from the online self-help training or not. Methods/Design A multi-centre, parallel-groups, randomised controlled trial will be conducted to evaluate the (cost-) effectiveness of the CAREST-trial. A sample of 454 women with curatively treated breast cancer will be recruited from 8 hospitals in the Netherlands. Participants will be randomised to the intervention or usual care group (1:1). Self-report measures will be completed at baseline, 3 (post-intervention), 9, and 24 months. Primary outcome is FCR severity; secondary outcomes are healthcare costs, health status, and psychological distress. The online tailored self-help training "Less fear after cancer" is based on cognitive behavioural therapy and consists of 2 basic modules (psycho-education; basic principles of cognitive behavioural therapy) and 4 optional modules (rumination; action; relaxation; reassurance) to choose from. Each module consists of an informative part (texts, videos, audio files) and a practical part (exercises). For every patient, the intervention will be available for three months. Personal online support by an e-mail coach is available. Discussion Online self-help training may be an easy-accessible and cost-effective treatment to reduce the impact of FCR at an early stage in a large group of breast cancer survivors. A strength is the 24 months follow-up period in the health economic evaluation. The results of the study will provide information on the possible strengths and benefits of online self-help training for FCR in breast cancer survivors. Trial registration This study is registered at the Netherlands Trial Register (NTR4119, date registered: August 15, 2013).